Table of contents, editorial board, and other front matter - Hal R. Taylor (Journal of Applied Communications, 1983)
Editorial front matter and table of contents for vol.66, no.1, Jan-Mar (1983) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education